AL-QUR'AN DAN FENOMENA SALAH TULIS : (Studi atas al-Qur'an dalam Tradisi Lisan dan Tulisan) - Derhana Bulan Dalimunthe (QOF, 2019)
This paper aims to see how the phenomenon of mistakenly written of the Qur'an in the Muslim world took place. Realized or not, some Muslims are often wrong in writing verses of the Qur'an even though he memorized it. Based on historical analysis, this phenomenon is very likely to occur. The phenomenon of mistakenly written of the Qur'an was formed because of the dominance of transmitting the Qur'an orally, not writing. This transmission has been carried out since the time of the Prophet until now. Although the Qur'an is already in the tradition of writing, but true writing tradition is only to strengthen the allegiance of the Qur'an. Then how much public awareness of oral and written traditions also influenced him. For those who have only consciousness, written oral misconduct is commonplace. However, for those who have written consciousness, mis-writing is taboo. In the Muslim community itself the written consciousness has not yet dominated in its society in full.